Pengaruh Penggunaan Model Pembelajaran Course Review Horay Berbantuan Multimedia Terhadap Prestasi Belajar Siswa Pada Pembelajaran IPA - Endah Sri Werdi Asih; Tria Mardiana; Ari Supriyatno (Universitas Muhammadiyah Magelang, 2019)
This study aims to determine the effect of the Multimedia-assisted Course Review Horay model on student achievement in science learning. This research was conducted in the fourth grade of SDN Krincing, Secang District, Magelang Regency, 2016/2017 Academic Year. The type of research used in this research is Quasi Experiment with Matching Pretest-Posttest Control Group Design. Learning in the experimental group by conducting three meetings, which was given treatment using the Horay Course Review Model. Pretest was given before treatment and posttest was given after treatment was given. The subjects in this study were 20 students in the experimental group and 20 students in the control group. The sampling technique in this research is saturated sampling. The sampling technique in this research is total sampling. There are two variables used in this study, namely the independent variable in the form of the Course Review Horay method assisted by Multimedia, and the dependent variable in the form of student achievement in science learning. Data collection techniques in the form of tests and observations. Analysis of the data obtained by using the Mann Whitney U Test. The results showed that the Course Review Horay method assisted by Multimedia had a positive effect on students' science learning. Based on the results of the posttest Mann Whitney U Test of the two groups conducted by the researcher, it was obtained that tcount < ttable, namely 0.013 <0.05. These results indicate that the Course Review Horay learning model assisted by Multimdeia has a significant effect on students' science learning achievement.